Design and Integration of Molecular‐Type Catalysts in Fuel‐Cell Technology. Issue 10 (19th June 2018) - Jose, Vishal; Elouarzaki, Kamal; Fisher, Adrian C.; Lee, Jong‐Min
Abstract: The field of molecular electrocatalysis research includes a wide range of emerging technologies that utilize molecular catalysts to catalyze anodic and/or cathodic reactions within a fuel‐cell setup, and has developed greatly in the last 10 years. Although the vast majority of fuel cells utilize noble metals as catalysts, several systems have been recently developed that are based on molecular catalysts. The focus here is on the integration of molecular catalysts in a fuel‐cell setup, which is contextualized, and which is named as "fuel‐cell‐based molecular‐type catalysts" here. The latter utilize a wide variety of chemical compounds, such as organometallics and organic or bioinspired compounds, to harvest chemical energy to generate current. Here, the state‐of‐the‐art for all molecular catalysts that convert chemical energy in a fuel‐cell setup is discussed and a novel classification system is presented to illustrate how molecular catalysts integrate into the broad field of fuel cells. The current performance of molecular catalysts in systems that use different fuels is summarized, and finally, for the first time, the achievable power outputs of fuel cells using uniquely molecular catalysts are presented. Abstract : Molecular catalysts catalyze anodic and cathodic reactions in fuel cells. The reactions are carried out through chemical compounds that are developed from organometallics to organic or bioinspired compounds. The performance of such catalysts in power produced through various fuel cells is studied and different catalysts are compared.